Spray Gel Formulation of Goroho Banana (Musa acuminata L.) Peel Extract: Optimization and Wound Healing Activity Analysis - Madeleine Trisha Salainti; Sri Hartati Yuliani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Goroho banana (Musa acuminata L.) peel extract has been traditionally used in Minahasa for wound healing. This study aimed to develop and optimize a spray gel formulation containing Goroho banana peel extract and evaluate its wound healing activity. A factorial design was employed with two factors (Carbopol 940 and HPMC) at two levels. Preliminary testing determined 3% as the optimal extract concentration through wound healing evaluation in rats. Four spray gel formulations were developed and characterized for physicochemical properties, including viscosity, pH, and drying time. Results showed Formula B (Carbopol 0.5% and HPMC 0.6%) exhibited optimal characteristics with viscosity 223.8 ± 7.6 cPs, pH 5.13 ± 0.05, and drying time 4.22 ± 0.05 minutes. The HET-CAM irritation test revealed mild irritation scores (2.5-3.8) for all formulations, with Formula B showing the lowest score (2.5). Design Expert optimization generated 100 solutions, with the optimal formula containing Carbopol 0.670% and HPMC 0.517%. The wound healing activity showed no significant differences between spray gel formulations and Bioplacenton (p0.05), indicating comparable efficacy. This study demonstrates the successful development of a safe and effective spray gel formulation of Goroho banana peel extract for wound healing applications.